2017
DOI: 10.1016/j.prosdent.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of treatment outcomes for facial prostheses in patients with craniofacial defects: A pilot retrospective study

Abstract: Patients should be recalled frequently so that retouches can be performed, avoiding the repeated fabrication of new prostheses. Well-designed studies are necessary to identify more relevant complications and factors that lead to prosthetic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 23 publications
0
32
0
3
Order By: Relevance
“…To the authors' knowledge, this is the first clinical report to describe 3D CBCT use for both (a) assessment of soft‐tissue and temporal bony topography and (b) 3D‐printing of soft‐tissue and bone surgical guides for an auricular prosthesis. Clinically reliable auricular replacement has been reported as early as 2002 1‐6,8,10‐13 . More prospective studies assessing multilevel 3D anatomic visualization are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors' knowledge, this is the first clinical report to describe 3D CBCT use for both (a) assessment of soft‐tissue and temporal bony topography and (b) 3D‐printing of soft‐tissue and bone surgical guides for an auricular prosthesis. Clinically reliable auricular replacement has been reported as early as 2002 1‐6,8,10‐13 . More prospective studies assessing multilevel 3D anatomic visualization are needed.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5 Of note, a 25-year retrospective analysis of 341 craniofacial implants in 110 patients by Subramaniam et al 11 , temporal implants overall showed the highest comparative success rate (97%) and statistically significant) prosthetic (P < .0001) and implant survival rates (P < .0001). Brandao et al 4 also reported an auricular implant success rate of over 98%; two-implant retention showed the lowest failure rate. While adhesive-and bar-retained prostheses have shown clinical success, 7,23,24 a 2012 review by Sharma et al 25 identified benefits of implant retention versus adhesive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação aos métodos de retenção, Papaspyrou et al 16 expuseram quatro técnicas de ancoragem de prótese disponíveis: o anatômico (usando estruturas já existentes), o mecânico (armações de óculos), o químico (usando adesivos) e a ancoragem cirúrgica (utilizando implantes de titânio). Brandão et al 9 enfatizaram ainda que a retenção da prótese é assumida como sendo o determinante primário de uma abordagem de sucesso e tem sido tradicionalmente alcançada usando adesivos ou óculos. No entanto, nenhum desses métodos fornece retenção satisfatória e duradoura.…”
Section: Caso Clínicounclassified
“…Próteses faciais de silicone têm sido propostas como as melhores abordagens para reabilitação de pacientes com defeitos craniofaciais, entretanto a longevidade e manutenção destas próteses são as principais preocupações dos clínicos e dos pacientes que receberão a reabilitação 9,10 . Esta deve ser confeccionada de modo a respeitar as etapas clínicas e laboratoriais e realizando todos os ajustes para que fique esteticamente satisfatória.…”
Section: Introductionunclassified